"Flipped Lid" Fracture of the Lateral Tibial Plateau with Dislocated Lateral Meniscus: A Case Report. Issue 1 (19th January 2023) - Kambhampati, Srinivas B.S.; Chodavarapu, Mounika N.S.; Kambhampati, Anirudh P.S.; Chittoor, Sai Prasad; Chinta, Shyam Kumar
Abstract : Case: We present a rare "flipped lid" type of fracture of the lateral tibial plateau with dislocation of the lateral meniscus into the notch with intact roots. This was fixed using headless screws through arthrotomy and peripheral suturing of the meniscus. At the 1-year follow-up, although there was terminal restriction of 10° flexion with redislocation of the lateral meniscus, the patient was able to perform all daily activities and declined further surgery. Conclusion: Flipped lid–type fracture is rare and results in good outcome when fixed early. Meniscal dislocation repair requires close monitoring to detect failure.